PAUD sebagai Ruang Inklusif dan Budaya Sekolah Ramah Anak - Azizah Hanum; Ihsania Torfi Rangkuti; Putir Salsabila; Sahara Putri (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Early Childhood Education (PAUD) is a crucial stage in shaping children’s cognitive, social, emotional, and moral development. The concepts of inclusive PAUD and child-friendly schools are key approaches to creating a learning environment that is safe, comfortable, and accepting of all children without discrimination. However, its implementation in Indonesia still faces challenges such as teachers’ limited understanding of inclusive learning, inadequate facilities, and a school culture that does not yet fully value diversity. This study aims to explore the concepts of inclusive ECE and child-friendly schools, a school culture that values diversity, as well as the roles of teachers and the school environment in fostering an inclusive climate. The study employed a qualitative method using a literature review approach. Data were collected from relevant journals, books, and scientific articles and analyzed using descriptive qualitative methods. Research findings indicate that inclusive early childhood education and child-friendly schools have a mutually supportive relationship in creating a child-centered educational environment. A school culture that values diversity plays a crucial role in fostering attitudes of tolerance, empathy, and respect for differences from an early age. Furthermore, teachers play a central role in fostering an inclusive classroom atmosphere through adaptive and non-discriminatory teaching strategies, while the school environment supports this through policies, facilities, and a positive school culture. The conclusion of this study indicates that the successful implementation of inclusive early childhood education and child-friendly schools requires synergy among teachers, schools, parents, and the surrounding community in creating a safe, comfortable, and diversity-respecting educational climate so that all children can develop optimally without discrimination.